A MALDI-TOF mass spectrometry-based method for detection of copy number variations in BRCA1 and BRCA2 genes - Zhou, Hongjun; He, Xin; Zhao, Jiadong; Mei, Zhu; Zhang, Xiayan; Yuan, Wen; Dong, Hui (Frontiers in Molecular Biosciences, 2024)
Background: Identifying germline mutations in BRCA1 and BRCA2 genes (BRCAs) would benefit the carriers in multiple aspects. In addition to singlenucleotide variations and small indels, copy number variations (CNVs) is also an indispensable component of identifiable mutations in BRCAs. A sensitive, rapid and throughput-flexible method to detect CNVs would be preferred to meet the rising clinical requirements for BRCAs testing.We developed a MALDI-TOF-MS-based method (MS assay) which included three steps: first, multiplex end-point PCR followed by a single base extension reaction; second, automated analyte transfer and data acquisition; third, data analysis. We applied MS assay to detect CNVs in BRCAs in 293 Chinese patients with ovarian or pancreatic cancer. All the samples were examined by targeted next-generation sequencing (TS) simultaneously. Samples were further cross-validated by multiplex ligation-dependent probe amplification (MLPA) if the results from MS assay and TS were inconsistent. Long range PCR was then applied to identify the exact breakpoints in BRCAs.Results: MS assay introduced highly multiplexed panels to detect CNVs of BRCAs semi-quantitatively. Simplified on-board data analysis was available for MS assay and no complex bioinformatics was needed. The turnaround time of MS assay was less than eight hours with a hands-on time of only 40 minutes. Compared to TS, MS assay exhibited higher sensitivity (100% vs 75%) and was more flexible in 4 throughput, with the reagent cost per sample remaining constant no matter how many samples were examined per assay. A total of eight CNVs in BRCAs were detected from the 293 samples, and the molecular breakpoints were successfully identified in five samples through long-range PCR followed by Sanger sequencing.Our results suggested that MS assay might be an effective method in primary screening for CNVs in genes such as BRCAs, especially when short turnaround time and/or high sensitivity is a top priority.